Pengaruh Kebijakan Hutang, Kebijakan Dividen dan Earning Per Share (EPS) Terhadap Nilai Perusahaan(Studi Empiris Pada Perusahaan Manufaktur Sub Sektor Pertambangan yang Terdaftar di Bursa Efek Indonesia Periode 2016-2020) - Khoirul Anam; Ronny Malavia Mardani; Etty Saraswati (UNIVERSITAS ISLAM MALANG, 2022)
Abstract The main goal of the company is to increase the value of the company. The purpose of this study was to determine the partial and simultaneous effect of debt policy, dividend policy, and earnings per share (EPS) on the values of mining companies listed on the Indonesia Stock Exchange (IDX) in 2016 – 2020. The method in this study using analysis. multiple linear regression. The results of this study indicate that the debt policy as measured by DER has a negative and significant effect on firm value as measured by PBV and dividend policy as measured by the DPR has a negative and insignificant effect on firm value as measured by PBV. While earnings per share as measured by EPS has a positive and significant effect on firm value as measured by PBV. For investors who will analyze the factors using firm value, dividend policy, dividend policy, and earnings per share (EPS) so that the investment made can be optimal. Keywords : debt policy, divident policy, earning per share, and company value.